Membrane rafts and caveolae in cardiovascular signaling - Insel, Paul A. (2009)
PURPOSE OF REVIEW: Substantial evidence documents the key role of lipid (membrane) rafts and caveolae as microdomains that concentrate a wide variety of receptors and post-receptor components regulated by hormones, neurotransmitters and growth factors. RECENT FINDINGS: Recent data document that those microdomains are important in regulating vascular endothelial and smooth muscle cells and renal epithelial cells, and in particular in signal transduction across the plasma membrane. SUMMARY: Raft/caveolae domains are cellular regions, including in cardiovascular and renal epithelial cells, that organize a large number of signal transduction components, thereby providing spatially and temporally efficient regulation of cell function.